Accountability Ecosystems: The Evolution of a Keyword - Halloran, Brendan (Accountability Research Center, 2021)
Efforts to strengthen the accountability of the governing to the governed go back millennia. However, in the past decade there has been a renewed debate about how to advance public accountability. One domain where this conversation has taken place is that of efforts funded by donors (government development agencies and private philanthropies), primarily in the Global South and implemented by a set of national and international actors, including NGOs, private sector project implementors, and international institutions. Unfortunately, much donor-funded work has been underpinned by an understanding of accountability grounded in optimistic assumptions, particularly around the role of transparency and information technology. Early efforts by Rosie McGee and John Gaventa to take stock of this work highlighted the lack of theories of change grounded in a more nuanced, holistic and politically-informed understanding of accountability. Others began questioning the dominant ‘transparency + participation = accountability’ formulation that underpinned many projects; and most of them were just that, projects: start date, end date, work plan, logical framework, funding proposal, budget, etc. It was at the beginning of this discussion about what it takes to achieve real accountability that the term ‘Accountability Ecosystem’ started being used by a few individuals and organizations. The organization I worked for at the time, the Transparency and Accountability Initiative (TAI), had picked up the term, potentially from the organization I work for now, the International Budget Partnership (IBP).[i] I saw the term as a way to advance a more holistic and dynamic way to talk about the interaction of accountability actors, mechanisms and efforts in a given context, and a deliberate step away from more simplistic, linear formulations.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização

Regional Integration at the Forefront of Mozambique’s Energy Success - Hundermark, Charnè (cnbcafrica, 2021)
As one of leading resource-rich countries in sub-Saharan Africa, Mozambique has the potential to not only significantly advance its own socioeconomic status, but also dramatically boost economic growth throughout the region. According to the World Bank Group, regional integration helps countries to overcome divisions that impede the flow of goods, services, capital, people and ideas. As large-scale energy projects are expected to come online in Mozambique through 2023, the country has observed renewed political commitment to establishing sustainable regional integration with neighboring governments and private operators.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; L - english / inglês; economic development / desenvolvimento económico

Signing of Grant Agreement with Mozambique: Contributing to the improvement of people’s living environment in Niassa Province through the construction of a rural water supply facility - JICA (2021)
On February 26, 2021, the Japan International Cooperation Agency (JICA) signed a grant agreement with the Government of the Republic of Mozambique in Maputo, to provide grant aid of up to 2.076billion yen for the Project for the Construction of a Rural Water Supply Facility in Niassa Province. Under this project, people’s living environment in Niassa Province will improve through installing a rural water supply facility, which will allow access to safe and clean water. It is expected that this project will lead to reduction of waterborne diseases and nutritional improvement. Measures to combat climate change will also be conducted, and this project will contribute to the achievement of SDGs Goals 3, 6, and 13.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; access to services / acesso a serviços; climate change / mudanças climáticas; infrastructure / infrastrutura

Mozambique’s insurgency: a new Boko Haram or youth demanding an end to marginalisation? - Hanlon, Joseph (Africa at LSE, 2018)
Joseph Hanlon argues that Mozambique’s new “Islamic” insurgency is about marginalised youth demanding to be heard, and therefore is similar to anti-establishment protest across the world.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Development for Whom?: From the Case of the ProSAVANA Project in Mozambique – Master of Development Practice - Go Suzui
ProSAVANA project in Mozambique There are tremendous numbers of development projects all over the world. Mozambique is one of the least developed countries. A serious issue in Mozambique is food security. Even though 80 percent of the labor force in Mozambique engages in agriculture (USAID 2017), Mozambique’s farmland is tropical savanna that features very poor soil quality, and Mozambique does not have technologies to overcome this issue. As related to a food security issue, more than two out of five children under five years old are malnourished in Mozambique (UNICEF Mozambique 2017). The government of Mozambique decided to transform the current agriculture system and ensure food security. ProSAVANA is a triangular cooperation program among Mozambique, Brazil and Japan since 2009. The Japan International Cooperation Agency, the Japanese Ministry of Foreign Affairs and the Brazilian Cooperation Agency have participated in this project. The main purpose is to “improve the livelihood of inhabitants of the Nacala Corridor through inclusive and sustainable agricultural and regional development” and to “create employment through agricultural investment and establishment of a supply chain,” (ProSAVANA 2016). It seems that ProSAVANA has positive impacts on agriculture and on the total GDP of Mozambique and can improve childhood nutrition.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; government policy / politica governamental

Deviations between the Planned and the Execution Undermine the Health Budget – Observatório do Cidadão para Saúde - Observatório Cidadão para Saúde
In Mozambique, health services are mostly provided by the public sector, and it is the responsibility of the Ministry of Health (MISAU) to enable the creation, planning and control of national health policies. The health sector is the third sector that absorbs most resources from the State Budget (OE), followed by the Education and Infrastructure sectors, according to the methodology presented in the budget documents related to the economic and social sectors. This sector is divided into three levels: namely, the Central Level, which is represented by MISAU; The Provincial Level, which is represented by the Provincial Health Directorates (DPS); and Finally, we have the District Level, which is represented by the Health, Women and Social Action Secretariats (SDSMAS). Therefore, it will be based on these levels that our analysis of allocations to the health sector in the period from 2015 to 2020 will be undertaken.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento; health - health services / serviços de saúde